Digital Transformation in Pharmaceutical Manufacturing Processes Based on Good Manufacturing Practice - Andari, Susilowati (Sciences and Clinical Pharmacy Research Journal, 2026)
This study aims to analyze the role of digital transformation in pharmaceutical manufacturing processes based on Good Manufacturing Practice (GMP) with a focus on its contribution to quality improvement, operational efficiency, and regulatory compliance. The study uses a qualitative approach with a descriptive method through a literature review, which involves analysis of scientific articles, official reports, and relevant academic documents published between 2015 and 2025. Data collection techniques were carried out through systematic searches of literature from various academic databases, while data analysis was conducted through the stages of theme identification, data reduction, concept categorization, and inductive conclusion drawing. The results of the study show that the integration of digital technologies such as Artificial Intelligence (AI), Internet of Things (IoT), blockchain, digital twins, and big data analytics significantly improves the effectiveness of GMP implementation by strengthening data integrity, accelerating data-driven decision making, and increasing the transparency of the pharmaceutical supply chain. However, obstacles such as organizational resistance, limitations of legacy system integration, and cybersecurity issues remain major challenges in its implementation. Theoretically, this study expands the understanding of the evolution of digital-based quality systems in the pharmaceutical industry, while practically providing strategic guidance for companies and regulators in designing sustainable and regulatory-compliant digital transformation policies. Thus, the results of this study make an important contribution to strengthening the conceptual and implementational framework of digital transformation in the global pharmaceutical sector.